Five and Ten Years on: Have DSR Standards Changed? - Venable, John (Springer, 2015)
It has been more than ten years since the publication of Hevner et al [1] and five years since Venable [2] surveyed editors and DSR researchers on standards and criteria for judging the quality and suitability of DSR submissions for publication. Since then, there has been much further discussion about evaluation, design theory, and standards for DSR publication. This paper attempts to answer the question of how standards for judging the quality (e.g., rigour and relevance) of DSR research publications have changed since 2010 and to develop a snapshot of the relative importance of different extant DSR publication criteria. To do so, the author surveyed editors of IS Scholars’ “basket-of-eight” journals, DESRIST conference program committee members, and DESRIST (co-)authors. This paper compares the quantitative findings of the current survey to the 2010 survey.